Big Data and Artificial Intelligence: Implications and Strategies for Business Development in Indonesia - Sahetapy, Hugo; Halik, Maria Yessica; Sino, Hendi William; Bokau, Joe Roland Setiyawan (Journal of Marketing Management and Innovative Business Review, 2025)
The rapid development of digital technology has significantly influenced business growth in Indonesia. Big Data and Artificial Intelligence (AI) have emerged as crucial tools in optimizing decision-making, improving operational efficiency, and enhancing business competitiveness. This study aims to conduct a Systematic Literature Review (SLR) to analyze the utilization of Big Data and AI in business development in Indonesia. The research identifies key benefits, challenges, and strategies for technology adoption. The findings highlight that Big Data enables businesses to extract valuable insights from vast datasets, while AI facilitates automation and predictive analytics to enhance marketing strategies, customer experience, and supply chain efficiency. However, several challenges hinder widespread adoption, including limited digital infrastructure, a shortage of skilled professionals, high investment costs, and regulatory concerns regarding data security and privacy. The study suggests that strengthening digital literacy, improving technological infrastructure, and fostering collaboration between government, academia, and industry are critical to accelerating the adoption of these technologies. By leveraging Big Data and AI effectively, businesses in Indonesia can enhance their competitive advantage and drive sustainable economic growth in the digital era.